Soil pollution and remediation: emerging challenges and innovations - Chen, Hao; Gao, Bin; Li, Yuncong (Frontiers in Environmental Science, 2025)
This perspective addresses the critical issue of soil pollution, exacerbated by rapid urbanization, intensive agriculture, and climate change, which introduces a complex mix of contaminants such as heavy metals, pesticides, per- and polyfluoroalkyl substances, and microplastics into the soil. These pollutants pose severe risks to environmental health and agricultural productivity by altering soil functionality and contaminant mobility. This perspective summarizes innovative monitoring and remediation technologies, including advanced sensors and bioremediation strategies, that enable real-time detection and effective management of soil pollutants. The integration of artificial intelligence and machine learning offers significant advancements in predicting and managing soil contamination dynamics. Furthermore, the perspective discusses the challenges and future directions in soil pollution research, particularly the need for robust policy frameworks and international cooperation to effectively manage and mitigate soil contamination. Emphasizing a multidisciplinary approach, this study calls for enhanced global standards, public engagement, and continued scientific research to develop sustainable solutions for soil remediation and to ensure the protection of vital soil resources for future generations.